Learners’ motivation, gender and oral english performance among high-ability students in Ibadan, Nigeria (2020)
This study examines predictive influence of motivation and gender on Oral English performance among students noted for high ability in Ibadan. Oyo State. The study adopted a descriptive survey of correlation type. Purposive sampling technique was used in selecting four public and private secondary schools in Ibadan North and Akinyele Local Government Areas with an aggregate number of 258 high-ability students. Instruments utilised were: English Language Screening Achievement Test (r=0.72). Achievement Test on Oral English (r=0.84) and Academic Motivation Questionnaire (r=0.84). Data were analysed, using Pearson Product Moment Correlation, Independent t-test and Multiple Regression Analysis. Learners’ motivation predicts Oral English performance among high-ability students (r=.54l. n=258. p<.05), but gender does not predict Oral English performance among the students (Crit-t 1.96, Cal. T = 0.097, p>.05). There is a joint contribution of learners’ motivation and gender to the prediction of Oral English performance (F(5 41) ='52.872, R2 = 0.54, p<.05) among the respondents. Intrinsic and extrinsic motivation of high-ability male and female learners should be meticulously worked upon by all stakeholders involved in the Oral English instruction of students noted for superior ability in our schools.